Study on Renewal Strategy of Traditional Villages in Beijing Suburbs from the Perspective of Catalytic Effect - A Case Study of Shuiyu Village in Fangshan District - OUYANG, Wen; SHI, Zuozheng; GUAN, Yujun (MAJ - Malaysia Architectural Journal, 2025)
The countryside represents the eternal noble spirit of the country. Due to the rapid industrialization and urbanization, the mass migration of population has led to the gradual transformation of traditional villages into "hollow villages". From the emergence of "nostalgia" culture to the proposal of "rural revitalization strategy", how to protect and develop traditional villages better has become an important proposition. As we all know, the depression of traditional villages has many reasons involving social structure and economic structure, and only the renewal of architecture and planning can not fundamentally save traditional villages. Therefore, the revival of traditional villages needs a complete and feasible system to provide theoretical support and experience reference. This paper takes traditional villages in the suburbs of Beijing as the research scope, and summarizes the classification, development status and characteristics of them through the research of existing literature and field research. Based on the urban catalyst effect, the paper puts forward the relevant renewal strategy of traditional villages in the suburbs of Beijing, including three core operations: "mining catalyst point", "shaping catalyst media" and "sustaining catalyst effect". Taking the renovation project design of Shuiyu Village in Fangshan District of Beijing as a practical case, the renewal research of traditional village is carried out from two aspects: the construction of material form catalyst and the strengthening of non-material form catalyst. This paper attempts to protect the cultural value, ecological value, economic value and life value of traditional villages by exploring the renewal of traditional villages in the suburbs of Beijing from the perspective of catalyst effect, and provide reference and inspiration for traditional villages in other regions.